2016
DOI: 10.1194/jlr.m064089
|View full text |Cite
|
Sign up to set email alerts
|

Exocytosis of macrophage lysosomes leads to digestion of apoptotic adipocytes and foam cell formation

Abstract: Many types of apoptotic cells are phagocytosed and digested by macrophages. Adipocytes can be hundreds of times larger than macrophages, so they are too large to be digested by conventional phagocytic processes. The nature of the interaction between macrophages and apoptotic adipocytes has not been studied in detail. We describe a cellular process, termed exophagy, that is important for macrophage clearance of dead adipocytes and adipose tissue homeostasis. Using mouse models of obesity, human tissue, and a ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
106
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 100 publications
(108 citation statements)
references
References 43 publications
2
106
0
Order By: Relevance
“…Previous studies showed that lysosomal exocytosis by macrophages is required for them to clear dead adipocytes (Haka et al, 2016). Since macrophages (~20µm diameter) are much smaller than adipocytes (~120µm diameter), they cannot clear dead adipocytes through a traditional phagocytosis mechanism.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies showed that lysosomal exocytosis by macrophages is required for them to clear dead adipocytes (Haka et al, 2016). Since macrophages (~20µm diameter) are much smaller than adipocytes (~120µm diameter), they cannot clear dead adipocytes through a traditional phagocytosis mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…To this end, we used a more physiologically relevant co-culture assay (Haka et al, 2016) that quantifies i ) the delivery of lysosomal contents from macrophages to apoptotic 3T3-L1 adipocytes, and ii ) the subsequent accumulation of adipocyte-derived lipids in the macrophage (Fig. 2B).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Exophagy refers to a process in which large macromolecular substrates (such as aggregated LDL (agLDL) and dead/dying adipocytes) are degraded in a plasma membrane-bound extracellular compartment by extruded lysosomal contents (3538). The degraded proteins and lipids are subsequently taken up into cells via endocytosis.…”
Section: Resultsmentioning
confidence: 99%